The defi nition of a «mechanism to crime» and its systematic and structural analysis (Journal of actual problems of jurisprudence, 2019)
In the article on the basis of the semantic meaning of the term «mechanism», defi nes the concept of «mechanism of a counteraction criminality» as a unity regularly arranged and interconnected elements that determine the order of the state and non-state structures to counteract such negative social and legal phenomena as crime.The terms using in criminology theory to describe the activity of the state, aimed at neutralizing the crime is investigated by the term «war crime» in the context, as its positive reception and critical analysis on the part of criminologists are analyzed.Keywords: fi ght against crime, mechanisms to crime, crime prevention, law enforcement, criminogenic effects.